A Natural Experiment in Reform: Analyzing Drug Law Policy in New York City, New York, Quantitative Data, 2006-2012 - Parsons, Jim ([Verlag nicht ermittelbar], 2020)
On January 1, 2011, the Vera Institute of Justice (Vera) launched "A Natural Experiment in Reform: Analyzing Drug Law Policy in New York," which was funded by the National Institute of Justice, and conducted by Vera, with the John Jay College of Criminal Justice at the City University of New York, and the School of Criminal Justice at Rutgers University. This study sought to analyze the effects of recent changes in drug offense sentencing laws in New York State (NYS) and chronicle New York City's experience with drug law reform (DLR). This includes changes in sentencing outcomes for felony drug cases, reoffending, and cost implications, with the hope of informing NYS policy makers, and provide other states across the nation with research to inform their own DLR efforts. Specifically, this study revolves around the following objectives: 1) describe how the DLR is reflected in actual sentencing outcomes and the extent to which practices of judges, lawyers, and defense attorneys have shifted in response to the reforms; 2) investigate how treatment diversion impacts reoffending and 3) analyze the cost implications of changing drug law sentencing policies. Researchers analyzed administrative data to describe the impacts of reforms on sentencing decisions, collected New York City arrest data for drug felonies between October 1, 2006 and September 30, 2011, and evaluated outcome data measuring recidivism and costs between pre and post DLR periods. Numerous variables tracking offenders' progress through the criminal justice system were collected including admission to the Drug Treatment Alternative to Prison (DTAP) program, arrest and disposition jurisdictions, charges, sentencing, and drug court screening and admission. Arrestees' criminal history and rearrest figures, as well as their sex, race, and ethnic demographics were collected also.